Antimicrobial resistance profiles of methicillin resistant coagulase negative Staphylococcus at a reference laboratory in Sierra Leone: implications for infection control - Muhindo, Abraham Bwalhuma; Aliero, Adamu Almustapha; Jiba, Darlinda F.; Syalhasha, Festo Mwebaze (International Journal of Public Health Science (IJPHS), 2025)
Methicillin-resistant CoNS (MR-CoNS) are increasingly recognized as significant nosocomial pathogens. Sierra Leone lacks data on the prevalence and antibiotic-resistance patterns of these bacteria, which hinders a cross-sectoral approach to tackling antimicrobial resistance as well as regional and global health surveillance. We report on clinical multidrug-resistant MR-CoNS from Freetown, Sierra Leone, West Africa, as emerging pathogens. This study aimed to explore the prevalence and antimicrobial resistance profiles of MR-CoNS isolated from clinical samples in Freetown, Sierra Leone. A cross-sectional study was conducted at the reference laboratory from January 2025 to June 2025. Clinical samples submitted to the microbiology department were screened for Staphylococcus species, and isolates identified as coagulase-negative Staphylococci (CoNS) using standard microbiological techniques. Methicillin resistance in all isolates was tested with a 30 μg cefoxitin disc and further confirmed through an automated Scenker XK Microbial ID and AST system by measuring the minimum inhibitory concentration (MIC) with oxacillin. Antibiotic susceptibility profiles were determined using the Scenker XK Microbial ID/AST system following the Clinical and Laboratory Standards Institute (CLSI) guidelines, and data were analysed using SPSS ver 16. Findings from our study show a prevalence of 18.2% of MR-CoNS with Staphylococcus schleiferi, (26.9%) predominant. Linezolid, vancomycin, and teicoplanin exhibited 100% activity against all the MR-CoNS isolated. However, there was co-and multidrug resistance exhibited to commonly known antibiotics gentamycin (75-100%), levofloxacin (80-100%), clarithromycin (87-100%), including resistance to newer antibiotics as daptomycin (33-50%).